2012
DOI: 10.1111/j.2042-7158.2011.01414.x
|View full text |Cite
|
Sign up to set email alerts
|

Aliskiren as a novel therapeutic agent for hypertension and cardio-renal diseases

Abstract: Objectives High blood pressure (BP) is a major risk factor for cardiovascular and renal complications. A majority of treated hypertensive patients still complain of high BP. The renin-angiotensin aldosterone system (RAAS) has been a centre-stage target for all the cardiovascular and cardio-renal complications. Aliskiren, is the first direct renin inhibitor (DRI) to be approved by the US FDA. Renin controls the ratelimiting step in the RAAS cascade and hence is the most favorable target for RAAS suppression. Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 103 publications
(197 reference statements)
0
4
0
Order By: Relevance
“…Several clinical studies with aliskiren in hypertensive patients without renal impairment showed its satisfactory antihypertensive effects [6,11,12,18,[21][22][23][24]. The lack of a significant BP decrease in our study might have been due to several reasons including relatively well-controlled BP with conventional therapy at baseline and the dose of aliskiren Table 2.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Several clinical studies with aliskiren in hypertensive patients without renal impairment showed its satisfactory antihypertensive effects [6,11,12,18,[21][22][23][24]. The lack of a significant BP decrease in our study might have been due to several reasons including relatively well-controlled BP with conventional therapy at baseline and the dose of aliskiren Table 2.…”
Section: Discussionmentioning
confidence: 62%
“…Aliskiren is currently the only drug from this class. So far several studies have shown that aliskiren effectively decreases blood pressure with the side-effect profile similar to placebo [8,11,12]. Since aliskiren is excreted with bile and does not require dose reduction in case of decreased glomerular filtration rate it could become a preferred drug for the treatment of hypertension in end-stage kidney disease [10].…”
Section: Introductionmentioning
confidence: 99%
“…While a large body of scientific data confirms independent renin inhibitory activity of linoleic acid [23][24][25] but there is no literature that provides strong support for the current results, showing α-linolenic acid ester as renin inhibitor. When compared to a clinical renin inhibitor, aliskiren (IC 50 0.6 nM), with bioavailability 2.6% [26] these esterified compounds may exhibit higher bioavailability leading to renin inhibition in vivo. Overall, the IC 50 values indicated a common feature in both series of compounds, i.e., the stronger renin inhibitory potential of esterified flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike angiotensin-converting enzyme inhibitors, direct renin inhibitors act on a specific single target [5], showing the potential to block the renin-angiotensin-aldosterone system to a fuller extent [6]. The therapeutic benefit of direct renin inhibition has been well established for the treatment of hypertension, heart failure and nephropathy [7]. …”
Section: Introductionmentioning
confidence: 99%